2010
DOI: 10.1007/s00192-009-1091-7
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation and cardiac pacemakers

Abstract: Sacral neuromodulation appears to be safe in the setting of cardiac pacemakers without cardioversion/defibrillation technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The patients were monitored during the second stage and the first round of programming postoperatively. Additionally, Roth [6] reported 5 patients with cardiac pacemakers who underwent staged implants under local sedation. Intraoperative cardiac monitoring and postoperative telemetry did not demonstrate cross-interference with the test stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were monitored during the second stage and the first round of programming postoperatively. Additionally, Roth [6] reported 5 patients with cardiac pacemakers who underwent staged implants under local sedation. Intraoperative cardiac monitoring and postoperative telemetry did not demonstrate cross-interference with the test stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Only SNM is currently FDA approved for treatment of bladder dysfunction. Roth [21] published a small case series showing that SNM could be used safely in conjunction with a cardiac pacemaker. A unique series of two patients with prior bladder augmentation and persistent symptoms by Rasmussen and colleagues [22] showed that SNM was an effective treatment after failed bladder augmentation.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Others include coagulation disorders and local acute sacrum infection. SNM appears to be safe in the presence of a cardiac pacemaker without cardioversion/ defibrillation technology (Wallace et al, 2007) (Roth, 2010). Some conditions are considered challenging as MRI & pregnancy; however, more details are discussed upcoming in the chapter.…”
Section: Contraindicationsmentioning
confidence: 99%